Electrostatic discharge prevention system via body potential control based on a triboelectric nanogenerator. (1st December 2022) - Lee, Cheoljae; Heo, Minsu; Park, Hyosik; Joo, Hyeonseo; Seung, Wanchul; Lee, Ju-Hyuck
Abstract: In modern society, electrostatic discharge (ESD) is frequently caused by humans charged with positive charges by contact electrification, wherein natural grounding is difficult. ESD not only makes our skin uncomfortable but can also lead to the destruction of small electronic components, fires, and explosions. Therefore, there is a continuous demand for technology, such as an ungrounded anti-static method, to prevent static electricity as the grounding method is inconvenient. This study demonstrates an ESD prevention system (EPS) using a triboelectric nanogenerator (TENG), which is ungrounded and does not require an additional power source. The developed EPS prevents ESD by supplying the negative charges generated from TENGs to the human body. Various factors were investigated to optimize the performance of the EPS. Using the TENG-based EPS, the electric potential that raised to 200, 500, and 1000 V was reduced to 0 V within 20, 31, and 38 s, respectively. Additionally, it succeeded in maintaining the electric potential of a body in a stable state by supplying negative charges generated by TENG, which is operated by the mechanical energy of the human body to compensate for the positive charges generated by contact electrification. This study provides a new design for ESD prevention devices that can be utilized in various industrial units, including semiconductors, petrochemicals, and chemicals, and for the general public. Graphical Abstract: The ungrounded electrostatic discharge (ESD) prevention system (EPS) using triboelectric nanogenerator (TENG) is introduced. The effect of output performance, discharger type and humidity on the efficiency of EPS was investigated. The proposed portable EPS will prevent electrostatic destruction, electrostatic explosion, and fire, which contribute to improving efficiency and preventing risks in various industries. ga1 Highlights: The ungrounded electrostatic discharge (EDS) prevention system (EPS) using triboelectric nanogenerator is introduced. The effect of output performance, discharger type and humidity on the efficiency of EPS was investigated. We demonstrated EPS system mounted shoes to prevent EDS.